The Terms Framework Formation for E-Learning in Pedagogical Science and Practice - MINICH, OKSANA A. (The journal of contemporary issues in business and government, 2021)
The article discusses the concept of ‘e-learning’ from the point of logical and semantic analysis. The formation of the ‘e-learning’ concept in the context of information development and communication technologies and their implementation in the educational process is analyzed. The ambiguity of understanding the meaning of ‘e-learning’ and ‘distance learning’ terms are established, the relationship of electronic, computer, distance, mobile, mixed, online learning concepts is revealed. Among the meaningful features of the e-learning concept, there are semantic, logical, technological, and didactic aspects. The author concludes that the content of this concept is poorly developed at the didactic level, which leads to the risk of reducing the quality of teaching, ‘blurring’ the effect of e-learning in pedagogical practice. It is proposed to consider the formation of the concept of ‘e-learning’ as a separate new didactic category.